تقويم فعالية الحملات الإعلانية استناداً إلى الاستجابة السلوكية للمستهلك دراسة مسحية لاستجابات المستهلكين في مدينة اللاذقية نحو إعلانات التلفاز السوري عن اللصاقة الطاقية - سليطين فاطر (Latakia University Journal - Economic and Legal Sciences Series, 2018)
هدف البحث إلى التعرف على كيفية تقويم فعالية الحملات الإعلانية عموماً، ثم ركز على أهم النماذج المستخدمة في تقويم هذه الفعالية؛ استناداً إلى الاستجابة السلوكية للمستهلك. تم التطبيق على الحملة الإعلانية عن اللصاقة الطاقية في التلفاز السوري. وقد صُممت الاستبانة بما يتفق مع نموذج AIDA المستخدم في تقويم فعالية الإعلان، ومُسحت استجابات المستهلكين باستخدام عينة عشوائية مؤلفة من 387 مستهلك في مدينة اللاذقية. وقد توصل البحث إلى النتائج الآتية: 1- حققت الحملة الإعلانية الفعالية في مجالي: جذب انتباه المستهلك إليها، وإثارة اهتمامه بموضوعها. 2- لم تحقق الحملة الإعلانية الفعالية في مجالي: خلق الرغبة لدى المستهلك بالشراء، ودفعه للشراء الفعلي ( أو للتفكير بالشراء مستقبلاً ) للأجهزة الكهربائية وفقاً لمعيار اللصاقة الطاقية. وقد اقترح البحث عدداً من التوصيات، التي من المتوقع في حالة تطبيقها؛ أن تساعد في تحسين فعالية الحملات الإعلانية المستقبلية حول موضوع اللصاقة الطاقية، أو المواضيع المشابهة. This research aimed to know how we can evaluate the effectiveness of advertising campaigns in general, then it focused on the most important models; that are used in evaluating this effectiveness depending on consumer’s behavioral response. The application has been applied on the advertising campaign about the energy label in the Syrian television. The questionnaire was designed according to AIDA model; that is used in evaluating advertising effectiveness, and The survey has been done toward the consumers responses; by using a random sample consisted of 387 consumer in lattakia city. The research results were: 1- the advertising campaign achieved the effectiveness in attracting consumer’s attention to it, and in triggering consumer’s interest to its subject. 2- the advertising campaign did not achieve the effectiveness in creating consumer’s desire to buy, and in leading consumer toward action for actual buying ( or thinking to buy in the future ) the electrical appliances according to energy label standard. The research suggested a number of recommendations, that if they are applied, they may be helping in improve the effectiveness of advertising campaigns in the future about energy label subject, or about the similar subjects.